2021
DOI: 10.1038/s41591-021-01497-1
|View full text |Cite
|
Sign up to set email alerts
|

CAR T cells with dual targeting of CD19 and CD22 in pediatric and young adult patients with relapsed or refractory B cell acute lymphoblastic leukemia: a phase 1 trial

Abstract: Chimeric antigen receptor (CAR) T cells targeting CD19 or CD22 have shown remarkable activity in B cell acute lymphoblastic leukemia (B-ALL). The major cause of treatment failure is antigen downregulation or loss. Dual antigen targeting could potentially prevent this, but the clinical safety and efficacy of CAR T cells targeting both CD19 and CD22 remain unclear. We conducted a phase 1 trial in pediatric and young adult patients with relapsed or refractory B-ALL (n = 15) to test AUTO3, autologous transduced T … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
97
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(117 citation statements)
references
References 31 publications
0
97
1
2
Order By: Relevance
“…Our preliminary underlying mechanism suggests that CAR19 and CAR22 T cells sequentially infused had consistent biological contributions, transcriptional patterns, and clinical relevance with the response or resistance to CAR-T cell therapy (unpublished data) . However, the dual CAR targeting strategy includes co-administration or co-transduction of two separate CAR T-cells, T cells transduction using a bicistronic plasmid encoding both CARs, or utilization of a tandem CAR 36 . Novel dual-targeting approaches are being actively examined in preclinical and clinical studies, and the optimal strategy remains undefined and comparatively assessed for clinical benefits 31 , 36 , 37 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our preliminary underlying mechanism suggests that CAR19 and CAR22 T cells sequentially infused had consistent biological contributions, transcriptional patterns, and clinical relevance with the response or resistance to CAR-T cell therapy (unpublished data) . However, the dual CAR targeting strategy includes co-administration or co-transduction of two separate CAR T-cells, T cells transduction using a bicistronic plasmid encoding both CARs, or utilization of a tandem CAR 36 . Novel dual-targeting approaches are being actively examined in preclinical and clinical studies, and the optimal strategy remains undefined and comparatively assessed for clinical benefits 31 , 36 , 37 .…”
Section: Discussionmentioning
confidence: 99%
“…However, the dual CAR targeting strategy includes co-administration or co-transduction of two separate CAR T-cells, T cells transduction using a bicistronic plasmid encoding both CARs, or utilization of a tandem CAR 36 . Novel dual-targeting approaches are being actively examined in preclinical and clinical studies, and the optimal strategy remains undefined and comparatively assessed for clinical benefits 31 , 36 , 37 .…”
Section: Discussionmentioning
confidence: 99%
“…In the case of B-ALL, CD19 and CD22 dual CAR-T cells were evaluated in clinical trials (NCT03233854, NCT03289455). Despite the promising results from in vitro and in vivo studies [ 245 ], relapses were observed in approximately 50% of the patients [ 246 , 247 ].…”
Section: New Car-t Targets Explored In Hematological Malignanciesmentioning
confidence: 99%
“…mantle cell lymphoma (NCT 04234061) and TRAN-SCEND FL (NCT04245839) is investigating CAR-T therapies in follicular lymphoma. Also, the TRAN- NCT04007029); 3) T-cell engineering with only one vector encoding both CARs (bicistronic CAR-T) (38). The latter strategy may lead to a less expensive and more homogeneous product and is therefore regarded as a very promising approach.…”
Section: Ongoing Trials Of Cd19 Car-t Cellmentioning
confidence: 99%